Expanding Coverage to Low-Income Childless Adults in Massachusetts: Implications for National Health Reform - Long, Sharon K (Health Serv Res, 2014)
OBJECTIVE: To draw on the experiences under Massachusetts's 2006 reform, the template for the Affordable Care Act (ACA), to provide insights into the potential impacts of the ACA Medicaid expansion for low-income childless adults in other states. DATA SOURCES/STUDY SETTING: The study takes advantage of the natural experiment in Massachusetts and combined data from two surveys—the Massachusetts Health Reform Survey (MHRS) and the National Health Interview Survey (NHIS)—to estimate the impacts of reform on low-income adults. STUDY DESIGN: Difference-in-differences models of the impacts of health reform, using propensity-score reweighting to improve the match between Massachusetts and the comparison states. DATA COLLECTION/EXTRACTION METHODS: Data for low-income adults are obtained by combining data from the MHRS and the NHIS, where the MHRS provides a relatively large Massachusetts sample and the NHIS provides data for samples in other states to support the difference-in-differences model. Supplemental data on county economic and health care market characteristics are obtained from the Area Health Resource File. PRINCIPAL FINDINGS: There are strong increases in coverage and access to health care for low-income adults under health reform in Massachusetts, with the greatest gains observed for childless adults, who were not eligible for public coverage prior to reform. CONCLUSIONS: In the states that implement the Medicaid provisions of the ACA, we would expect to see large increases in coverage rates and commensurate gains in access to care for low-income childless adults. Linking state and federal surveys offers a strategy for leveraging the value of state-specific survey data for stronger policy evaluations.